Incidencia del gasto público social en la reducción de la pobreza en colombia (2017)
Article is a preliminary preview of the results of a further study on the incidence it has had in Colombia public social spending on poverty reduction. The results so far suggest that different factors have influenced in the structure and territorial distribution of poverty in Colombia, among which is the expenditure of public resources that by constitutional and legal mandate should be aimed at mitigating poverty levels in the country.